(K, Na)NbO3-based ceramics with excess alkali oxide for piezoelectric energy harvester. Issue 4 (March 2016) - Kim, J.H.; Kim, J.S.; Han, S.H.; Kang, H.-W.; Lee, H.-G.; Cheon, C.I.
Abstract: (K0.44 Na0.52 Li0.04 )(Nb0.86 Ta0.1 Sb0.04 )O3 (KNLNTS) ceramics were prepared by a solid-state reaction. The effect of excess (K, Na)2 O alkali oxide on the densification, phase evolution, microstructure development, and piezoelectric properties was investigated. The figure of merit (FOM) (d33 ·g33 ) for piezoelectric energy harvesting applications was also compared between the samples with and without excess alkali oxide. The addition of the excess alkali oxide changed the tetragonal crystal structure to orthorhombic and decreased the sintering temperature by about 100 °C. The dielectric constant of the orthorhombic phase is much lower than that of the tetragonal phase. The orthorhombic sample with excess alkali oxide sintered at 1020 °C demonstrated higher FOM in spite of having a smaller piezoelectric constant (d33 ) than the stoichiometric sample sintered at 1100 °C. This result indicates that a KNN ceramic with an orthorhombic composition near the MPB with a moderate piezoelectric constant and smaller permittivity is more advantageous for an energy harvesting application than that with a morphotropic phase boundary (MPB) or a tetragonal composition.